Effectiveness of the Implementation of Semarang Mayor Regulation Number 27 of 2019 on Plastic Usage Control in Semarang City Area - Made Wipra Pratistita; Dino Riska Afdhali; Atik Winanti (Fakultas Hukum Dehasen, 2023)
This article is based on the existence of plastic which is one of the wastes from appropriate technology that is often used by humans.Focus in this article about amount to increase plastic waste in Semarang city over 3 years and implementation of regulation for all subyect bussiness targets in Semarang City. Therefore, this regulations are formed to reduce the generation of consume plastics in Semarang City. The purpose of this study is to determine to effectiveness of implementation of the mayor regulation of the city of semarang number 27 of 2019 as an effort to reduce consume plastic for to reduce the amount plastic waste in Semarang City. The legal research method used is empirical with the legal data analysis method that is descriptive qualitative. The results of this research are the conclusion is that the implementation of Semarang Mayor Regulation no. 27 of 2019 because there has been no reduction in the amount of plastic waste generated in Semarang City in 2019 -2020.